COMPARISON OF MICROSTRUCTURES AND OXIDATION BEHAVIORS OF YTRIA AND MAGNESIA STABILIZED ZIRCONIA THERMAL BARRIER COATINGS (TBC) - Doleker, Kadir Mert; Ozgurluk, Yasin; Özkan, Derviş; Mesekiran, Nihal; Karaoğlanlı, Abdullah Cahit; Özgürlük, Yasin; Karaoğlanlı, Abdullah Cahit; Özkan, Derviş (Inst Za Kovinske Materiale I In Tehnologie, 2018)
Thermal barrier coatings (TBCs) provide protection to minimize aggressive environmental conditions such as oxidation, corrosion and thermal shocks occurring at high temperatures. In this study, a CoNiCrAlY metallic-bond coat was deposited on an Inconel 718 superalloy substrate with a thickness about 100 mu m using the atmospheric-plasma-spray (APS) method. The production of TBCs was accomplished by depositing Y2O3 partially stabilized zirconia (YSZ) and MgO-stabilized zirconia (MSZ) as two different ceramic top-coating materials, having the total thickness of 300 mu m. The specimens were subjected to a metallographic investigation before the oxidation tests; their surface roughness, porosity, hardness and microstructural properties were investigated and then compared with the results obtained after the oxidation tests. The TBC systems were subjected to isothermal-oxidation tests at 900 degrees C and 1000 degrees C for (8, 24, 50 and 100) h. After the oxidation tests, XRD, SEM and EDX elemental analyses were carried out and the changes in the thickness and structure of the thermally grown oxide (TGO) layer were investigated. A remarkable change occurred between the top and the bond coat in the TBC systems depending on the increasing time and temperature. The TGO layer thickness showed an increase. At the interface, Al2O3 and other mixed-oxide layers occurred. Before and after the oxidation, XRD analyses showed that YSZ, had a tetragonal phase and a bit of a monoclinic phase. The MSZ coating included tetragonal, monoclinic and cubic phases at the end of the oxidation. This phase transformation causes a large volume increase in an MSZ lattice. Due to this volume increase, MSZ coatings suffer more damage than YSZ coatings.
Keywords: Atmospheric Plasma Spray; Thermal Barrier Coatings; Oxidation; Zro2-Y2o3; Zro2-Mgo